The Regulation Paradox of Initial Coin Offerings: A Case Study Approach - Zhang, Alfred Ruoxi; Raveenthiran, Anujan; Mukai, Justin; Naeem, Ramisha; Dhuna, Arvin; Parveen, Zoha; Kim, Henry (Frontiers in Blockchain, 2019)
Compared to initial public offerings (IPOs) that are sales of company ownerships, and loans that are sales of debt claims, initial coin offerings (ICOs) are sales of promises of cryptocurrency appreciation. However, regulatory uncertainties continue to prohibit successful widespread adoption. This paper examines ICOs with varying levels of success, including Mastercoin (now Omni) and Kin, as well as fraudulent ICOs, like REcoin and OneCoin. The discussion of the benefits and flaws within the ICO market examines regulatory challenges concerning risks transferred to investors through information asymmetry, while questioning the ability of regulations to enhance investor protection mechanisms without undermining the fundamental value of cryptocurrencies and ICOs as a viable funding structure.